2021
DOI: 10.3390/ma14051126
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Sulfate and Plasma Rich in Growth Factors Enhance Bone Regeneration after Extraction of the Mandibular Third Molar: A Proof of Concept Study

Abstract: The aim of this study was to evaluate the mixture of Calcium Sulfate and Plasma Rich in Growth Factors (CaSO4 + PRGF) as a bone-graft substitute in extracted mandibular third molar (MTM) alveoli during a 4-month period. Bilateral MTM extractions were performed in 10 patients (18–25 years) at the Oral-Surgery-Clinic of the Universidad Autónoma de Yucatán (UADY). A CaSO4 + PRGF mixture was placed in the right alveolus (Experimental Group (EG)) and a natural blood clot in the left (Control Group (CG)). Monthly X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A recent study used combination of CS spheres with plasma rich in growth factors (PRGF) as a bone-graft substitute following removal of mandibular third molar [ 56 ]. The authors reported that the grafted sites showed significant bone regeneration compared to control sites.…”
Section: Calcium Compoundsmentioning
confidence: 99%
“…A recent study used combination of CS spheres with plasma rich in growth factors (PRGF) as a bone-graft substitute following removal of mandibular third molar [ 56 ]. The authors reported that the grafted sites showed significant bone regeneration compared to control sites.…”
Section: Calcium Compoundsmentioning
confidence: 99%
“…PRGF is a very small section of centrifuged blood containing Platelet-derived growth factors A and B (PDGF-A, PDGF-B), vascular endothelial growth factor (VEGF), BMP-2, transforming growth factor-beta (TGF-β), and insulin growth factor (IGF). These growth factors play a critical role in bone regeneration [ 19 21 ]. So, the application of PRGF in bone regeneration is increasing [ 22 ].…”
Section: Introductionmentioning
confidence: 99%